On Container Versus Time Based Inspection Policies in Invasive Species Management - Amit Batabyal; Peter Nijkamp (European Regional Science Association (ERSA), 2005)
We study the problem of precluding biological invasions caused by ships transporting internationally traded goods in containers between different regions of the world. Using the long run expected net cost (LRENC) of inspections as the apposite managerial objective, we address the following important question: Given that inspection is a cyclical activity, is the LRENC lower when a port manager's inspector inspects cargo upon the arrival of a specified number of containers (container policy) or is this LRENC lower when this inspector inspects cargo at fixed points in time (temporal policy)? We construct a queuing theoretic model and show that in an inspection cycle, irrespective of whether the inspection policy choice is made on the basis of an explicit optimization exercise or on the basis of rules of thumb, the container policy is superior to the temporal policy because the container policy results in lower LRENC from inspection activities.
Keywords: 330